Inequality and Employment Resilience: An Analysis of Spanish Municipalities during the Great Recession. (January 2021) - Geelhoedt, Fabian; Royuela, Vicente; Castells-Quintana, David
In this paper we study an association almost neglected in the literature, that between income inequality and resilience. In particular, we explore the response of employment rates in the face of the crisis of 2008 and how income inequality levels may have affected this response. To do so, we construct two measures of employment resilience—resistance and recoverability—using data on total employment and self-employment for 995 Spanish municipalities during the Great Recession. Our results provide evidence of the threats that high levels of inequality pose for employment resilience, showing that average income is the most important mediating factor of this association.